1990
DOI: 10.1063/1.344743
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Sm-Fe-Ti-Al sputtered films with i H c greater than 30 kOe

Abstract: Recently the synthesis of a new high intrinsic coercive force, iHc=38.5 kOe at 293 K, Sm-Fe-Ti phase in film form was reported. Films with Al additions have now been made, and the preparation conditions are better defined. The addition of 2.3–4.5 at. % Al helped to sharpen the x-ray patterns of the high iHc samples. The iHc values for Al concentrations less than 4 at. % did not fall below 30 kOe for proper preparation conditions. The nominal composition for the high iHc phase samples spanned from 17 to 22 at. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Sm meets this demand. Actually, high-coercive-force Sm-Fe-Ti alloys have been produced by sputtering [8], mechanical alloying [9], melt-spinning [10], and conventional powder metallurgical method [11]. Careful investigation of the x-ray diffraction patterns of these Sm-Fe-Ti alloys [12] showed that they have Nd 5 Fe 17 type structure.…”
Section: Introductionmentioning
confidence: 99%
“…Sm meets this demand. Actually, high-coercive-force Sm-Fe-Ti alloys have been produced by sputtering [8], mechanical alloying [9], melt-spinning [10], and conventional powder metallurgical method [11]. Careful investigation of the x-ray diffraction patterns of these Sm-Fe-Ti alloys [12] showed that they have Nd 5 Fe 17 type structure.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous thin-film alloys of rare earth (RE) and transition metals (TM) are a new type of materials which show very high magnetic anisotropy [1,2]. Depending on the thickness of layers, the rate of deposition and the temperature of the substrate, RE-TM multilayered systems exhibit a large variety of magnetic properties.…”
mentioning
confidence: 99%